Strengthening the Curriculum of the Islamic Education Management Study Program Through Analysis of Graduate Tracer Study Results - Safitri, Ajeng; Hasan, Yetri; Fadilah, M. Kharis; Tuala, Riyuzen Praja (STAI Serdang Lubuk Pakam, 2024)
The findings of the tracer study have the potential to strengthen the curriculum, but often the results are just administrative fulfillment, with regard to that this study aims to analyze the results of the tracer study as a basis for strengthening the curriculum of the Islamic education management study program at UIN Raden Intan Lampung. The research method used is qualitative with a descriptive study approach. Data collection is done through observation, interviews, and documentation studies. The results showed that Islamic education management graduates are relevant to industry needs, with high job absorption and suitability of fields. Stakeholders assess soft skills as good, but foreign languages and innovation need to be improved. Tracer study is important for curriculum evaluation, although it has not been maximized. Steps to strengthen the curriculum can include revising materials, improving training, and integrating labor market needs. The implication of this research is to contribute to the development of deeper insights into the use of tracer studies as an instrument for evaluating the effectiveness of curriculum strengthening, especially in the context of the Islamic Education Management Study Program.